2005
DOI: 10.1080/09593332608618554
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Approach for Abattoir Wastewater Treatment

Abstract: Detailed physico-chemical studies on abattoir effluent using lime, alum, ferrous sulphate and an anionic polyelectrolyte were tried individually and in combination. Among the coagulants tried, lime resulted in good settling of the sludge. At 400 mg l(-1) of lime dose, the Suspended Solids (SS), Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) removals were found to be 41.9%, 38.9% and 36.1%, respectively. Best results were obtained with lime and ferrous sulphate in a combination ratio of 400:10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 6 publications
0
15
0
4
Order By: Relevance
“…Abattoir wastewater contains high-strength organic nitrogen (N), total nitrogen (TN) being in the range of 150-400 mg/l [4]. In intermittently aerated treatment processes, nitrate (NO 3 --N) is produced by means of nitrification during the aeration periods [4][5][6]. However, limited investigations have been carried out on the isolation of nitrifying bacteria from slaughter house wastewater, few examples being, Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Abattoir wastewater contains high-strength organic nitrogen (N), total nitrogen (TN) being in the range of 150-400 mg/l [4]. In intermittently aerated treatment processes, nitrate (NO 3 --N) is produced by means of nitrification during the aeration periods [4][5][6]. However, limited investigations have been carried out on the isolation of nitrifying bacteria from slaughter house wastewater, few examples being, Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 98%
“…In few cases, the waste is chemically coagulated and flocculated before discharge into the sewers [2]. Wastewater from a typical abattoir in India possesses chemical oxygen demand (COD) concentration in the range of 4,400-18,000 mg/l [3]. Blood, one of the major dissolved pollutants in slaughterhouse wastewater, has a COD of 375,000 mg/l.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium sulphate (alum) has been used for water purification since ancient times. However, some studies showed that using alum for abattoir wastewater treatment produces higher amount of sludge in comparison to ferrous sulphate and an anionic polyelectrolyte [23]. The addition of coagulant aids such as silica and activated carbon can help reducing sludge volume [24].…”
Section: Coagulation-flocculation-sedimentationmentioning
confidence: 99%
“…This wastewater is predominantly loaded with organic wastes and is rich in organic content (Bozinis et al, 1996). Biological treatment processes are widely used for the treatment of agro-industry wastewaters, such as tomato industry wastewater which contain high concentrations of biodegradable organic matter (BOM) (Satyanarayan et al, 2005;. Anaerobic treatment of high strength wastewater is widely accepted in the industry Mehrdad et al, 2007;Del Pozo et al, 2003;Bernet &Paul, 2006).…”
Section: Introductionmentioning
confidence: 99%